THE EFFECTIVENESS OF BLENDED LEARNING USING A LEARNING SYSTEM IN NETWORK (SPADA) IN UNDERSTANDING OF MATHEMATICAL CONCEPT - Marchamah Ulfa; Nicky Dwi Puspaningtyas (IAIN Ambon, 2020)
In this study, learning is carried out by Blended Learning (BL) with the SPADA in Calculus/ Mathematics courses in terms understanding of student concepts. This study aims to see the effectiveness of the application of learning with BL in terms of understanding students concepts. The study used a quasi-experimental technique with a population of all Indonesian Teknokrat University students. The sampling technique uses random sampling and to test its effectiveness a T-test statistic is used with α = 5%. Obtained student learning outcomes in the experiment class with an average of 78,48 higher than control class and standard deviation 9,96. Based on the results of the T test, it can be concluded that this learning is effectively applied. The conclusion of this study shows that the application of learning in BL is effective when viewed from the understanding of student concepts. This is because BL learning is able to combine face-to-face learning with learning in a network that is in accordance with the current development. Students are more interested and motivated to study hard and look for learning resources that are getting closer to them through devices or computers. Keywords: blended learning; concepts understanding; SPADA